(3GdcGaj aj GdMSGHs - (3CHh aNQ GdOjf eMeO Hf GdMSf, GdMGSH GdcQNjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdCSJGP CHh HcQ eMeO Hf GdMSjf GdcQLi GdMSGH QMeg Gddg aEf Chdi eG aJJM Hg GdcdGe hbVi Hg Mb GdEfYGe s
(3BNQgG (B:s
(3hMQQJg HdG QhjI hgh VGef deG jcai GdcGai ai QShe Ojfg hCMcGe Ojhfg Je GdcGai s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B((3MSGH (B20) s
Keywords: (3GdQjGVjGJs